A Retrospective Analysis of Polymer Selection Using Solvent Casting: Formulation and DoE Optimization of the Amorphous Solid Dispersion of Amoxicillin Trihydrate by a Spray Drying Method - Chetan Borkhataria; Hardik Chauhan; Bhargavi Mistry; Manisha Kalaria; Rachana Katbamana; Kalpesh Patel (International Journal of Chemical Engineering)
Background. Amoxicillin trihydrate possesses poor solubility, compressibility, and flow behavior. Amorphous solid dispersion prepared by spray drying could solve all three problems at the same time. Objective. To prepare amorphous solid dispersion after screening of polymers by solvent casting method using a spray drying method. Methods. The solvent casting method was used to screen polymers, PVP/VA S-630, PVP K30, Soluplus, PEG 4000, HPMC AS, and HPMC HP55, in 1 : 1 and 2 : 3 ratios and followed by spray drying after polymer selection. Results. The dissolution performance of the formulation improved with time. The optimum feed rate and feed concentration were found to have an impact on the flow properties and particle size of spray-dried formulations, and they were selected as independent variables in a 32 full factorial statistical design. The ANOVA and regression analysis suggest that the developed regression model has a significant overall fit to the data and can explain a substantial proportion of the variability in the dissolution at 10 minutes. The optimized batch was selected based on the decisive factors of minimum and maximum values of response variables. Overall, the optimized batch demonstrated improved characteristics in terms of percentage yield (32.81%), dissolution at 10 min (49.70%), and angle of repose at 31.42°. Conclusion. This study provides valuable insights into optimizing formulation strategies for preserving the amorphous state of drugs and contributes to the development of stable pharmaceutical formulations.